Postpartum Breastfeeding Promotion and Duration of Exclusive Breastfeeding in Western Nepal - Khanal, V.; Lee, A.; Karkee, R.; Binns, Colin (Blackwell Publishing Inc., 2015)
Background: Encouragement and skills provided to mothers during the postpartum period have been found to be successful in increasing exclusive breastfeeding rates. However, evidence from developing countries is limited. This study aimed to ascertain whether education and skill support provided by health workers during the postpartum period were associated with increased duration of exclusive breastfeeding in Western Nepal. Methods: A community-based prospective cohort study was conducted between January and October 2014, in the Rupandehi district of Nepal. Information on breastfeeding promotion provided by health workers after birth was collected from 649 mothers. The association between breastfeeding promotion and exclusive breastfeeding was investigated using multivariable Cox regression analysis. Results: Of the 649 mothers, 35 percent received all eight types of breastfeeding promotion advice, and 60 percent received six or more such types of advice. Breastfeeding promotion, such as "breastfeeding on demand" (hazard ratio [HR] 0.74 [95% CI 0.59-0.92]) and "not to provide pacifier or teats" (HR 0.82 [95% CI 0.68-0.97]), were significantly associated with a lower risk of exclusive breastfeeding cessation. The dose-response relationship was also significant for the number of advices received (HR 0.94 [95% CI 0.90-0.97]). Conclusions: This study provides evidence that breastfeeding education and support immediately after childbirth could increase the duration of breastfeeding. The results suggest further attention to breastfeeding promotion in all maternity hospitals and birthing centers through skilled birth attendants.